Anonimo Mexicano - Glass-Coffin, Bonnie (Utah State University, University Libraries, 2005)
Transcribed from the original Nahuatl manuscript (written circa 1600) and translated into English for the first time, this epic chronicle tells the preconquest history of the Tlaxcalteca, who migrated into central Mexico from the northern frontier of the Toltec empire at its fall. By the time of Cort